2011
DOI: 10.3390/catal1010040
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Reactions on Model Gold Surfaces: Effect of Surface Steps and of Surface Doping

Abstract: Abstract:The adsorption energies and the activation energy barriers for a series of reactions catalyzed by gold surfaces and obtained theoretically through density functional theory (DFT) based calculations were considered to clarify the role of the low coordinated gold atoms and the role of doping in the catalytic activity of gold. The effect of the surface steps was introduced by comparison of the activation energy barriers and of the adsorption energies on flat gold surfaces such as the Au(111) surface with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Secondly, Au-Pd/MC offered abundant acid sites, which might favor the contact between the catalyst and C-OH bond in the intermediates, thereby improving the yield of ketones. Thirdly, the Au nanocatalyst was known to have high O 2 activation ability and be effective in oxidizing various organic compounds with O 2 as the oxidant [49]. The introduction of Pd species would favor the O 2 activation to generate active oxygen species, leading to enhanced catalytic activity [30].…”
Section: Reaction Pathwaymentioning
confidence: 99%
“…Secondly, Au-Pd/MC offered abundant acid sites, which might favor the contact between the catalyst and C-OH bond in the intermediates, thereby improving the yield of ketones. Thirdly, the Au nanocatalyst was known to have high O 2 activation ability and be effective in oxidizing various organic compounds with O 2 as the oxidant [49]. The introduction of Pd species would favor the O 2 activation to generate active oxygen species, leading to enhanced catalytic activity [30].…”
Section: Reaction Pathwaymentioning
confidence: 99%
“…The first review article by Sun et al [1] covers aspects of atomically monodisperse gold nanoclusters, with precise core-shell structure, which are fundamental to design new types of highly active and selective gold catalysts for a variety of catalytic processes. The role of surface steps and surface doping in the catalytic reactions on model gold surface was addressed through Density Functional Theory (DFT) based calculations by Gomes and coworkers [2] in a second review. Recent developments on synthesis of gold catalysts supported on mesoporous silica were exhaustively reviewed by Belkacemi et al [3] who highlighted the importance of gold nanoparticles incorporation into the channels in order to prevent Au agglomeration and leaching.…”
Section: The Present Issuementioning
confidence: 99%
“…The release of pollutants from industries and other resources have increased the environmental problems. , The most noticeable contaminants are nitrogen oxides (NO, NO 2 , and N 2 O) which are mostly generated from combustion of fuel that contributes to the photochemical smog, acid rain formation, depletion of the ozone, and greenhouse effects. , Mostly, fuel combustion contains 95% NO and 5% NO 2 . NO is a hazardous gas which has an adverse effect on atmosphere, human respiratory system, and ecosystem. , Therefore, it is substantial to enterprise catalytic techniques to reduce or remove NO molecules from the atmosphere. In recent years, it is proved computationally and experimentally that the single metal atoms effectively anchored and stabilized on a suitable metal oxide surface or another metal supports for catalysis. Recently, Allard et al reported through theoretical modeling that the Pd single atom supported on the θ-Al 2 O 3 surface shows excellent catalytic performance for NO oxidation .…”
Section: Introductionmentioning
confidence: 99%